Anatomical variation of radial wrist extensor muscles: a study in cadavers (Clinics, 2008)
OBJECTIVE: The tendons of the extensor carpi radialis longus and brevis muscles are quite useful in tendon transfer, such as in correction of finger clawing and restoration of thumb opposition. Knowledge of additional radial wrist extensor muscle bellies with independent tendons is useful in the above-mentioned surgical procedures. METHODS: The skin, subcutaneous tissue, and antebrachial fascia of 48 (24 on the right side and 24 on left side) male upper limb forearms were dissected. The following aspects were then analyzed: (a) the presence of additional muscle bellies of radial wrist extensors, (b) the origin and insertion of the additional muscle, and (c) measurements of the muscle bellies and their tendons. RESULTS: Five out of 48 upper limbs (10.41%) had additional radial wrist extensors; this occurred in 3 out of 24 left upper limbs (12.5%) and 2 out of 24 right upper limbs (8.3%). In one of the right upper limbs, two additional muscles were found. The length and width of each additional muscle belly and its tendon ranged between 2 - 15cm by 0.35 - 6.4cm and 2.8 - 20.8cm by 0.2 0.5cm, respectively. The additional radial wrist extensor tendons in our study basically originated either from the extensor carpi radialis longus or brevis muscles and were inserted at the base of the 2nd or 3rd metacarpal bone. CONCLUSION: The present study will inform surgeons about the different varieties of additional radial wrist extensors and the frequency of their occurrence.